Liability of Marketplaces: A Comparative Analysis of Legal Approaches in the USA and France - A. A. Onianova (Цифровое право, 2025)
The article analyzes two opposing approaches to the liability of marketplaces for the sale of defective products in the U.S. and France. The purpose of the study is to compare these models of regulation and identify the peculiarities of the legal status of online platforms in these jurisdictions. The first part of the paper considers the American approach, according to which marketplaces can be held liable for the goods they sell. Doctrinal arguments that justify the possibility of qualifying marketplaces as responsible actors are presented. At the same time, it is emphasized that this approach has developed mainly at the level of case law and has not yet been reflected in legislation. The second part analyzes the French approach that assigns marketplaces the status of intermediaries who are not responsible for the quality of products sold. The key example is a case in which one of the largest marketplaces in Europe, Fnac, was exempted from liability for selling defective products. The author critically analyzes this decision, noting the paradox of French regulation: initially oriented towards enhanced consumer protection, it tends to weaken it in the context of marketplaces. Special attention is paid to the doctrinal distinction between obligations of results and obligations of means. Applying the criteria developed in the doctrine to the circumstances of the case at hand allows us to conclude that the obligation of the marketplace corresponds to the model of the obligation of results. Finally, based on the comparison of different legal regimes, a conclusion is drawn about the advisability of applying Article 1240 of the French Civil Code as a basis for holding the aggregator liable.